Shakespeare, music and performance - Barclay, Bill 1980-; Lindley, David (Cambridge University Press, 2017)
"Music has been an essential constituent of Shakespeare's plays from the sixteenth century to the present day, yet its significance has often been overlooked or underplayed in the history of Shakespearean performance. Providing a long chronological sweep, this collection of essays traces the different uses of music in the theatre and in film from the days of the first Globe and Blackfriars to contemporary, global productions. With a unique concentration on the performance aspects of the subject, the volume offers a wide range of voices, from scholars to contemporary practitioners (including an interview with the critically-acclaimed composer Stephen Warbeck), and thus provides a rich exploration of this fascinating history from diverse perspectives" --Provided by publisher.